A model-based integrated assessment of land degradation by water erosion in a valuable Spanish rangeland - Ibáñez, J; Contador, J F Lavado; Schnabel, S; Fernández, M Pulido; Valderrama, J Martínez (Environmental Modelling & Software, 2014)
This paper presents an integrated assessment model aimed at evaluating land degradation by water erosion in dehesa rangelands in the Iberian Peninsula. The model is built following the system dynamics approach. The degradation risk is likened to the probability of losing a certain amount of soil within a number of years, as estimated over a great number of stochastic simulations. Complementary indicators are the average times needed to lose different amounts of soil over the simulations. A group of exogenous factors are ranked in order of importance. These factors are mainly climatic and economic and potentially affect soil erosion. Calibration is carried out for a typical dehesa defined over 22 working units selected from 10 representative farms distributed throughout the Spanish region of Extremadura. The degradation risk turns out to be moderate. The importance of climatic factors on soil erosion considerably exceeds that of those linked to human activities.
Keywords: Dehesa rangeland; Integrated assessment model; Land degradation; soil erosion; System dynamics